Chemical composition of Mozzarella cheese manufactured by Solanum dubium coat extract and chymosin - Yassin, Husham Ahmed Mohamed; Abdalla, Mohamed Osman Mohamed; El Owni, Osman Ali Osman (Journal of Veterinary Medicine and Animal Production, 2021)
This study was conducted to evaluate the effect of coagulant type (Solanum dubium, coat extract and chymosin) on the chemical composition of Mozzarella cheese. The cheese was manufactured, using Solanum dubium extract and chymosin as coagulants, stored for 28 days and the chemical composition (fat, total protein, ash, soluble protein and acidity) was determined at 1, 7, 21 and 28 days- intervals. The results showed that the coagulant type significantly affected fat, total protein, and soluble protein contents, with the highest values being in cheese made with Solanum dubium coat extract (20.38, 30.72 and 0.52%, respectively). The storage period significantly affected fat, total protein, acidity and soluble protein contents. The fat and total protein contents slightly decreased at week 2 (17.75% and 25.31%, respectively), before decreasing towards the end of the storage period, while the acidity increased to the maximum at week 2 (1.01%), then gradually decreased towards the end. The soluble protein fluctuated during the storage period, increasing in week 2 (0.33%), followed by a decrease in week 3 (0.30%), then increased at the end. During the storage period, Mozzarella cheese made with Solanum dubium and chymosin separately, the fat content slightly increased towards the end (21.00% and 18.00%, respectively), while the total protein content slightly decreased at week 3 (27.55% and 26.77%, respectively), then increased. Total solids content of cheese made with chymosin slightly increased at week 3 (49.49%) then decreased, while that made with Solanum dubium coat extract steadily decreased towards the end. The ash content of cheese made with chymosin decreased to minimum at week 3 (1.90%), followed by an increase towards the end, while that of cheese made with Solanum dubium slightly increased at week 2 (2.22%), then decreased at week 3(2.05%) before slightly increasing again. The titrable acidity of cheese made with both coagulants followed the same trend, increasing at week 2 (0.74% and 1.28% for cheese made with Solanum dubium and chymosin, respectively) followed by a decrease at the end of thevstorage period, The soluble protein of cheese made with both coagulants slightly increased at week 2 (0.35% and 31% for cheese made with Solanum dubium and chymosin, respectively), then the solublity of cheese made with Solanum dubium increased towards the end, while that made with chymosin slightly decreased.